The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-356870/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe Congenital Neutropenia Due To G6PC3 Deficiency Case Series of Five Patients and Literature Review

Abstract: Glucose-6-phosphate catalytic subunit 3 (G6PC3) deficiency is characterized by severe congenital neutropenia with recurrent pyogenic infections, a prominent superficial venous pattern, and cardiovascular and urogenital malformations, caused by an alteration of glucose homeostasis, with increased endoplasmic reticulum stress and cell apoptosis. We describe five new cases from Mexico, and review 89 more patients reported in the past decade, to delineate the most frequent laboratory and genetic features, their tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In our group of patients, IVSV was a relatively common finding. Although patient four did not show this anomaly, veins may probably become more prominent with age 5 , being this finding present in two-thirds of patients 16 .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In our group of patients, IVSV was a relatively common finding. Although patient four did not show this anomaly, veins may probably become more prominent with age 5 , being this finding present in two-thirds of patients 16 .…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, our patients (Table 1) fulfilled the criteria for SCN and cyclic neutropenia, as all showed variable degrees of severe neutropenia associated with periods of remission and affected platelet and lymphocytes cell lines. Regarding non-hematological abnormalities, congenital heart defects were the most frequent, as others have noticed 16,19 . We found that in all positive cases presented with ASD, these defects usually occurred as soft murmurs or were asymptomatic for a long time, making them a common undiagnosed abnormality 20 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations